POTENTIAL OF GROWTH HORMONES IAA OF ENDOPHITIC MICROBES FROM NEEM PLANTS FOR CAPITAL OF INDUSTRIAL OPPORTUNITY - Sylvia J R Lekatompessy; Nuriyanah; Liseu Nurjanah; Eleazar Handoyo; Rumella Simarmata; Tiwit Widowati (BRIN, 2021)
Indonesia has a tropical climate that is rich in diversity of microorganisms with useful potential and has important values that can be developed in the fields of industry, health and agriculture. Neem is a plant commonly used as an insecticide for pest control. Biotechnology continues to develop in exploiting the unique and interesting potential of endophytic microbes to obtain useful bioactive compounds extracted from plants, without having to take large amounts of plant biomass. This study aims to explore other potentials of endophytic microbes from neem plants, namely as a producer of IAA growth hormone to support plant growth. The results of the test of growth hormone-producing microbes, from 19 isolates of endophytic bacteria tested, obtained 3 isolates of IAA hormone-producing bacteria. 36 isolates of endophytic fungi were tested, 18 isolates of endophytic fungi were positive for IAA hormone production. One of the isolates of endophytic fungi that produces the highest IAA hormone, has been identified molecularly and the result is Colletotrichum gloeosporioides. The potential value derived from the endophytic microbes of neem plants can be developed into biotechnology products that have high commercial value by utilizing potential genes to support plant growth.